2017
DOI: 10.18860/madrasah.v10i1.5093
|View full text |Cite
|
Sign up to set email alerts
|

Menumbuhkan Karakter Tanggung Jawab Melalui Buku Ajar Tematik Integratif Berbasis Karakter

Abstract: Teaching not only convey the content of the subject matter, but also interpreted as the process of character formation. At elementary school level learners need model more than cleverness. Growing the character of responsibilities can be done by teachers in several ways, one of them using textbooks integrative thematic teaching based on character. This textbook is structured on the basis of competence that is combined with the content of responsibility characters. This textbook is designed with interesting, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…which in the novel package class V has improved aspects of learning religious personality. The results of the trial conducted found textbooks significantly influence student character development (Syabrina & Sulistyowati, 2021). This textbook is designed according to the characteristics of grade 2 elementary school students by adhering to the rules of writing systematically and interestingly by paying attention to aspects of learning objectives that will be achieved.…”
Section: Emphasizing the Character Value Of Learnersmentioning
confidence: 99%
“…which in the novel package class V has improved aspects of learning religious personality. The results of the trial conducted found textbooks significantly influence student character development (Syabrina & Sulistyowati, 2021). This textbook is designed according to the characteristics of grade 2 elementary school students by adhering to the rules of writing systematically and interestingly by paying attention to aspects of learning objectives that will be achieved.…”
Section: Emphasizing the Character Value Of Learnersmentioning
confidence: 99%
“…The textbook can be used to raise students' awareness of the nation and state and to help them develop into good and intelligent citizens (Syabrina, 2017). Additionally, the textbook plays a critical role as a strategic medium that shapes students' interests, attitudes, and reasoning.…”
Section: Introductionmentioning
confidence: 99%